Cultural Conflict in “Alif Lam Mim” and “My Name is Khan” Movies - Sartika, Endang; Laelatul Hida, Sukma; Amalia Putri, Dewi; Alia Anzani, Rahma; Maesaroh, Siti (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
This study aims to analyze the social conflict in a film. The objects of this research are